Urban vs Rural Factors Associated with Anemia in Haitian School Children - Palacios, Ana (Curr Dev Nutr, 2020)
OBJECTIVES: Children from urban areas in Haiti have a higher prevalence of anemia vs. rural (71% vs. 51%, respectively). The objective of this study was to identify the mediating factors between urban-rural residence and anemia. METHODS: This cross-sectional study used baseline data from two clustered randomized controlled trials that assessed the efficacy of a nutrition intervention. A total of 981 children from Cap Haitien, and 300 children from rural areas of the same region were included. Generalized linear mixed models were conducted to identify associations with anemia. Models were adjusted for age, school cluster and income. Significant variables were then included in a mediation analysis to explore the relationship between place of residence and child anemia. RESULTS: The odds of anemia were 2.35 times greater in children from urban vs. rural areas. Older age was inversely associated with anemia in rural and urban children, [OR = 0.88 95% CI (0.81–0.96)] and [OR 0.93; 95% CI (0.88–1.00)], respectively. In rural areas, stunting increased the odds of anemia, [OR = 3.41; 95% CI (1.45–7.80)], while households with more adults lowered the odds, [OR = 0.74; 95% CI (0.62–0.98)]. In the urban context, the odds of anemia were greater when intestinal worm morbidities were reported, [OR 1.74; 95% CI (1.13–2.68)]. Among number of adults living in the household, stunting and intestinal helminth morbidities, the latter partially mediated the relationship between anemia and place of residence (P = 0.03). CONCLUSIONS: Younger children are at a higher odds of suffering anemia in both rural and urban contexts. In rural areas, stunting increased the odds of anemia, while larger households with more adults lowered it. Children with intestinal worm morbidities had a greater odds of anemia in urban locations, and mediated the relationship between anemia and place of residence. Findings from this study suggest the need to develop site-specific interventions in Haiti, highlighting the importance of additional, non-nutritional factors of anemia in this population. FUNDING SOURCES: The original trials received United States Department of Agriculture (USDA) Foreign Agricultural Service Micronutrient Fortified Food Aid Products program FFE-521–2012/034–00.